Persistence and recovery of introduced Rhizobium ten years after inoculation on Leucaena leucocephala grown on an Alfisol in southwetern Nigeria - Sanginga, N.; Danso, S.K.A.; Mulongoy, K.; Ojeifo, A.A. (1994)
Establishment of Leucaena leucocephala was poor at Ibadan (Transition forest-savanna zone) and Fashola (savanna zone, 70 km north of Ibadan) in southwestern Nigeria as a result of low soil fertility and the presence of only a few native rhizobia capable of nodulating it. Inoculation with L. leucocephala at these two locations in 1982 resulted in striking responses with Rhizobium strains IRc 1045 and IRc 1050 isolated from L. leucocephala grown in Nigeria. The persistence of inoculated effective Rhizobium strains after inoculation is desirable since it removes the need for reinoculation. Because of the perennial nature of L. leucocephala and its use in long-term alley farming experiments, we examined the persistence of inoculated rhizobial strains after inoculation, and their ability to sustain N2-fixation and biomass production at Ibadan. In 1992, ten years after Rhizobium introduction, uninoculated, L. leucocephala fixed about 150 kg N ha-1 yr-1 or about 41% of total plant N compared to 180 kg N ha-1 yr-1 or 43% measured in 1982. Serological typing of the nodules using the Enzyme-Linked-Immunosorbent Assay (ELISA) and intrinsic resistance to the streptomycin test revealed that most of the nodules (96%) formed on L. leucocephala in 1992 were by Rhizobium strains IRc 1045 and IRc 1050, which were inoculated in 1982. Nodules were absent on uninoculated L. leucocephala grown on the adjacent field with no history of L. leucocephala cultivation. We conclude that the N2 fixed by Rhizobium strains IRc 1045 and IRc 1050 persisted for many years in the absence of L. leucocephala and sustained effectively fixed N2 which growth and yield of L. leucocephala after several years, thus encouraging a possible low-input alley farming system by smallholder farmers in Nigeria.